Impact of government policies and investment agreements on FDI inflows - Rashmi Banga (Indian Council for Research on International Economic Relations (ICRIER), 2003)
The last two decades have witnessed an extensive growth in foreign direct investment (FDI) flows to developing countries. This has been accompanied by an increase in competition amongst the developing countries to attract FDI, resulting in higher investment incentives offered by the host governments and removal of restrictions on operations of foreign firms in their countries. This has also led to an ever-increasing number of bilateral investment treaties (BITs) and regional agreements on investments. In this scenario, the question addressed by the study is: How effective are these selective government policies and investment agreements in attracting FDI flows to developing countries and do FDI from developed and developing countries respond similarly to developing host countries' policies? To answer this, the study examines the impact of fiscal incentives offered, removal of restrictions and signing of bilateral and regional investment agreements with developed and developing countries on FDI inflows to developing countries, after controlling for the effect of economic fundamentals of the host countries. The analysis is first undertaken for aggregate FDI inflows to fifteen developing countries of South, East and South East Asia for the period 1980-81 to 1999-2000. Separate analyses are then undertaken for FDI from developed and developing countries. The results based on random effects model show that fiscal incentives do not have any significant impact on aggregate FDI, but removal of restrictions attracts aggregate FDI. However, FDI from developed and developing countries are attracted to different selective policies. While lowering of restrictions attract FDI from developed countries, fiscal incentives and lower tariffs attract FDI from developing countries. Interestingly, BITs, which emphasize non-discriminatory treatment of FDI, are found to have a significant impact on aggregate FDI. But it is BITs with developed countries rather than developing countries that ar found to have a significant impact on FDI inflows to developing countries
Keywords: F21; 330; Foreign Direct Investment; selective government policies; Bilateral Investment; Treaties; FDI from Developed and developing countries